Methodological basis for constructing a management system for a multi-level socio-economic system with information asymmetry - Gurtuev Alim; Makhosheva Salima; Ivanov Zaur; Khadzhieva Mariyam; Abazokov Mukhamed (E3S Web of Conferences, 2023)
The modern world economy is in a constant state of transformation, and innovation has become a key success factor for states, companies and individual entrepreneurs. However, innovation is not limited to just developing new products or technologies. They also include the creation and development of innovation systems that ensure effective interaction between various levels and subjects in the process of innovation. Multi-level innovation systems are a complex and important aspect of the modern economy. This article examines the key aspects of such systems, their role in stimulating innovation and economic development, the prospects and challenges they face, as well as the concept of multi-level innovation systems, and explores their importance, features and practical aspects in the modern world.